Rehabilitasi Pecandu Narkotika dan Korban Penyalahgunaan Narkotika Selama Proses Peradilan - Agatha Geraldine (Faculty of Law, Universitas Airlangga, 2022)
AbstractPlacement in medical rehabilitation and / or social rehabilitation institutions for Narcotics Addicts and Narcotics Abuse victims is not only done voluntarily or through a legal process after a verdict or ruling by a judge. Rehabilitation can also be carried out during the judicial process, namely from the process of investigation, prosecution and trial based on Government Regulation Number 25 of 2011 concerning the Implementation of Mandatory Reporting for Narcotics Addicts. Although rehabilitation during the judicial process has been stated in government regulations, this is not regulated in the Narcotics Law and in its implementation, institutions that receive the authority often abuse their authority in providing rehabilitation during the judicial process so that efforts are needed to prevent abuse of this authority.Keywords: Rehabilitation; Narcotics Addicts; Narcotics Abuse victims; Judicial Process. AbstrakPenempatan pada lembaga rehabilitasi medis dan/atau rehabilitasi sosial terhadap Pecandu Narkotika dan korban penyalahgunaan Narkotika tidak hanya dilakukan secara sukarela maupun melalui proses hukum setelah dijatuhkan putusan atau penetapan oleh hakim. Rehabilitasi juga dapat dilakukan selama proses peradilan berlangsung, yakni dari proses penyidikan, penuntutan, dan persidangan berdasarkan Peraturan Pemerintah Nomor 25 Tahun 2011 tentang Pelaksanaan Wajib Lapor Pecandu Narkotika. Walaupun rehabilitasi selama proses peradilan telah disebutkan dalam peraturan pemerintah, namun hal tersebut tidak diatur dalam UU Narkotika dan dalam pelaksanaannya seringkali lembaga yang mendapat kewenangan tersebut menyalahgunakan kewenangannya dalam memberikan rehabilitasi selama proses peradilan sehingga perlu dilakukan upaya untuk mencegah penyalahgunaan kewenangan tersebut. Kata Kunci: Rehabilitas; Pecandu Narkotika; Korban Penyalahgunaan Narkotika; Proses Peradilan.